Mapping Wuhan Morphological atlas of the Urbanization of a Chinese City - Bekkering, Henco (TU Delft Open, 2022)
Chinese cities have been expanding since the early 1980s under trends of rapid modernization, urbanization and globalization. Since then they have changed dramatically, and have in the process lost many of their traditional environments and spatial characteristics. Urban planners and designers have been and are facing unprecedented challenges in China. They not only have to learn to understand the constantly emerging new urban mechanisms, and seek balance among stakeholders, but they also need to cope with the political pressures and the changing context under often extreme time pressure. In such circumstances, future- and design-oriented analysis based on a designerly way of thinking is useful-if not indispensable-for understanding the existing city and deciding on its transformations in a responsible and accountable way that is communicable among designers and with the public. This is especially so, in light of the growing awareness-also in China-of the value and importance of local urban identity, that is always-at least partially-based on history. In this atlas the Delft method of historical morphological analysis is applied to the city of Wuhan, valuing the importance of and finding meaning in the local urban identity of a city with a population over 11 million with a floating population of 14 million. The series of maps show the urban development, covering a century and a half.